2002
DOI: 10.2105/ajph.92.4.624
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Racial Discrimination, Social Class, and Health Among Ethnic Minority Groups

Abstract: The different ways in which racism may manifest itself (as interpersonal violence, institutional discrimination, or socioeconomic disadvantage) all have independent detrimental effects on health, regardless of the health indicator used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
428
1
11

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 565 publications
(458 citation statements)
references
References 26 publications
18
428
1
11
Order By: Relevance
“…There is no shortage of studies documenting the relationship between this form of discrimination and compromised psychological wellbeing, psychosomatic symptoms and cardiovascular and psychological reactivity (Williams & Williams-Morris, 2000). The majority of these studies examine the health impact of discrimination in a US context among African Americans, although sexual orientation, social class, and gender are social categories also linked to instances of interpersonal discrimination (Karlsen & Nazroo, 2002;Laveist, Rolley, & Diala, 2003;Meyer, 2003a). Stigma researchers generally have two different ways of conceptualizing stigma as a psychosocial stressor, which are distinct from the types of stress induced by interpersonal discrimination.…”
Section: Bridging Stigma and Prejudice Research Traditionsmentioning
confidence: 99%
“…There is no shortage of studies documenting the relationship between this form of discrimination and compromised psychological wellbeing, psychosomatic symptoms and cardiovascular and psychological reactivity (Williams & Williams-Morris, 2000). The majority of these studies examine the health impact of discrimination in a US context among African Americans, although sexual orientation, social class, and gender are social categories also linked to instances of interpersonal discrimination (Karlsen & Nazroo, 2002;Laveist, Rolley, & Diala, 2003;Meyer, 2003a). Stigma researchers generally have two different ways of conceptualizing stigma as a psychosocial stressor, which are distinct from the types of stress induced by interpersonal discrimination.…”
Section: Bridging Stigma and Prejudice Research Traditionsmentioning
confidence: 99%
“…Related to this, there is some evidence that direct exposure to discrimination is associated with an increased likelihood of psychosis. For example, Karlsen & Nazroo (2002), in an analysis of data from the UK Fourth National Survey of Ethnic Minorities, found that both socio-economic position and the experience of discrimination were independent predictors of psychosis in Black and Minority Ethnic groups. Perhaps most intriguing is the finding that the relative risk of schizophrenia increases as Black Caribbean people in the UK form a decreasing proportion of the local population (Boydell et al 2001 ;Kirkbride et al 2007) ; that is, the less ethnically dense an area, the higher the rates of psychosis.…”
Section: Understanding the High Ratesmentioning
confidence: 99%
“…Moreover, when compared to the indigenous population, rates of health problems such as cardiovascular, musculoskeletal, and mental health disorders are high among immigrant groups and are likely to further increase because of the aging of these groups [1e5]. Explanatory factors may be poor working conditions [2,3], lack of physical activity [6], and difficulty in adapting to the new cultural environment which, in turn, hampers access to care [7]. Such health problems often lead to long-term functional limitations and high needs for health care [8e11].…”
Section: Introductionmentioning
confidence: 99%